Assessment of Motor Components in Relation to Structural and Functional Impairments in Individuals with Stroke - Kanase, Suraj; Aranake, Anubha; Coutinho, Tanishqa; Ambali, Manoj; Patil, Shrirang (Journal of Neonatal Surgery, 2025)
Background: Stroke often causes motor impairments like spasticity, weakness, and poor coordination, impacting functional independence. This study used Modified Ashworth Scale (MAS) and Electromyography (EMG) to assess neuromuscular dysfunction, providing insights into post-stroke motor deficits and structural and functional impairments secondary to stroke. Methodology: A total of 30 participants were selected based on the inclusion criteria. The study being an observational type the participants were analysed for wrist flexor spasticity with modified Ashworth scale [MAS] and electromyography [EMG]. Analysis:The selected outcome measures were analysed based on their reliability, validity, and clinical relevance. The relationship between motor impairments (muscle weakness, spasticity, coordination deficits) and structural-functional brain damage (corticospinal tract lesions, impaired neural connectivity) was examined. The effectiveness of these tools in capturing motor recovery and functional improvements was assessed. Results:Findings indicate a strong correlation between structural damage and motor impairments, with corticospinal tract lesions significantly affecting voluntary movement. Functional deficits, including impaired strength, power and mean amplitude were effectively captured through standardized assessments. The outcome measures demonstrated high reliability in tracking motor functional impairments due to structural impairments giving a positive correlation between MAS scores and EMG duration and negative correlation betweenMAS scores and EMG amplitude Conclusion: Standardized motor assessments are essential for evaluating structural and functional impairments in stroke survivors. Their integration into clinical practice enhances rehabilitation planning and patient outcomes. Future research should focus on refining these tools for more precise evaluation of motor recovery